PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - samnur saputra (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
The problem behind this research is the low level of students' mathematical understanding abilities. One alternative learning that can be applied to improve students' mathematical understanding abilities is the SFE learning model. The aim to be achieved in this study was to determine the effect of using the SFE learning model on improving students' mathematical understanding abilities. The method used in this study is a quasi-experimental method, with research design Non-Equivalent Control Group Design. The research was conducted at TULUS KARTIKA Middle School Bandung. The population in this study were all eighth grade students of SMP TULUS KARTIKA Bandung. The sample in this study were students of class VIII-A as the experimental class and class VIII-B as the control class. The instruments used are in the form of tests of mathematical understanding to determine students' mathematical understanding. Before testing hypotheses, an analysis of data normality and homogeneity is carried out first, both experimental and control classes. The data analyzed were the data from the test results of students' mathematical understanding abilities namely pretest, posttest and gain index. Based on the analysis of the results of the test of mathematical understanding ability, the conclusion is that the SFE learning model has a positive effect on improving students' mathematical understanding abilities, with medium category.